Optimization of pseudo‐continuous arterial spin labeling at 7T with parallel transmission B1 shimming - Wang, Kai; Ma, Samantha J.; Shao, Xingfeng; Zhao, Chenyang; Shou, Qinyang; Yan, Lirong; Wang, Danny J. J. (Magnetic resonance in medicine, 2022)
Purpose To optimize pseudo‐continuous arterial spin labeling (pCASL) for 7 T, and to further improve the labeling efficiency with parallel RF transmission transmit B1 (B1+) shimming. Methods pCASL parameters were optimized based on B1+/B0 field distributions at 7 T with simulation. To increase labeling efficiency, the B1+ amplitude at inflowing arteries was increased with parallel RF transmission B1+ shimming. The “indv‐shim” with shimming weights calculated for each individual subject, and the “univ‐shim” with universal weights calculated on a group of 12 subjects, were compared with circular polarized (CP) shim. The optimized pCASL sequences with three B1+ shimming modes (indv‐shim, univ‐shim, and CP‐shim) were evaluated in 6 subjects who underwent two repeated scans 24 hours apart, along with a pulsed ASL sequence. Quantitative metrics including mean B1+ amplitude, perfusion, and intraclass correlation coefficient were calculated. The optimized 7T pCASL was compared with standard 3T pCASL on 5 subjects, using spatial SNR and temporal SNR. Results The optimal pCASL parameter set (RF duration/gap = 300/250 us, Gave=0.6mT/m,gRatio=10) achieved robust perfusion measurement in the presence of B1+/B0 inhomogeneities. Both indv‐shim and univ‐shim significantly increased B1+ amplitude compared with CP‐shim in simulation and in vivo experiment (P < .01). Compared with CP‐shim, perfusion signal was increased by 9.5% with indv‐shim (P < .05) and by 5.3% with univ‐shim (P = .35). All three pCASL sequences achieved fair to good repeatability (intraclass correlation coefficient ≥ 0.5). Compared with 3T pCASL, the optimized 7T pCASL achieved 78.3% higher spatial SNR and 200% higher temporal SNR. Conclusion The optimized pCASL achieved robust perfusion imaging at 7 T, while both indv‐shim and univ‐shim further increased labeling efficiency.